Effect of zinc and molybdenum on the microstructure and corrosion behavior of magnesium-based alloys produced by powder metallurgy technique - Muhammad Ameerul Fikri, Romzi (2022)
Magnesium and its alloys offer lightweight and excellent material properties that are beneficial for automotive components, electronics, and biomedical applications. However, due to their hexagonal close-packed crystal structure, they generally exhibit limited ductility at low temperatures. The addition of alloying elements and reinforcement can effectively address this limitation, but the corrosion behavior can be significantly affected. In automotive industry, the estimated corrosion rate was about 8.5 μm/year. This study aims to investigate the microstructure development of magnesium (Mg) with the addition of zinc (Zn) and molybdenum (Mo). The corrosion behavior of Mg samples was evaluated with a correlation to their microstructure development. All of the samples were produced using the powder metallurgy technique, and the compact samples were produced based on 10, 20, and 30 wt. % of Zn and Mo compositions. The microstructure was investigated by optical and scanning electron microscopy, while the phase analysis was determined from X-ray diffraction analysis. The corrosion behavior was evaluated by the hydrogen evolution test and potentiodynamic polarization test in 3.5 wt.% sodium chloride (NaCl) solution. From the microstructure observation, great bonding and distribution of Zn in the Mg matrix were achieved when alloying with Zn, compared to Mg with Mo addition. Based on this finding, the corrosion resistance of Mg-Zn alloys is higher than Mg-Mo alloys. However, the samples were easily crack when observed during hydrogen evolution test. This condition has led to the enhancement of Mg-30Zn corrosion rate compared to Mg-10Zn and Mg20Zn. The addition of Mo serves as reinforcement particles in the Mg, inducing porosity in the sample and affecting the corrosion rate of the Mg sample by weight loss during exposure in the 3.5 wt. % NaCl solution. The corrosion resistance of Mg-Mo alloys increased with the increasing amount of Mo composition, which is associated with the less crack of the alloys. The Mg-5Zn-Mo sample has a lower corrosion rate than MgMo samples but a higher corrosion rate than Mg-Zn samples. The high corrosion rate of Mg-Zn-Mo samples is due to the compilation from the amount of Mo particles and the presence of MgZn2 precipitates thus causing easily crack or fracture during the corrosion test. In conclusion, considering the potential of alloying elements, it is possible to design a Mg alloy that satisfies both mechanical and corrosion properties for more extensive engineering applications. Therefore, this study is conducted to identify the effect of Zn and Mg addition towards the microstructure and corrosion behavior of Mgbased alloys produced by powder metallurgy technique.